Hubungan Pengarahan Ketua Tim Dengan Motivasi Perawat Di Ruang Rawat Inap - Novianisya Maharani Susanto; Iyos Sutresna; Heri Ridwan (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Nursing services with good team methods depend on the team leader's ability to direct their work in a motivated working environment. In fact, the direction has not been fully done by the team leader due to some factors such as a lot of work, and internal and external problems between the other nurses. This study aims to find out the link between the leadership of the team leader and the motivation of the nurse. This type of research is quantitative research with a cross-sectional study design. The sampling technique used is the total samplings of all associate nurses in the RSUD hospital room of Sumedang, which has a total of 160 people. Data collection used an adaptation of Murtiani's (2013) direction questionnaire and Saefuloh's (2009) motivation questionnaire. Data analysis technique using Spearman Rho. The results of univariate analysis of both variables showed that the majority of respondents under the leadership of the team leadership were 148 nurses (92,5%) and most of the respondents with a high motivation for work were 147 nurse (91.9%). Bivariat analysis indicated that a signifying value or p-value was obtained (0,001) < (0,05), meaning that there was a significant relationship between team leader leadership and nurse motivation at RSUD Sumedang. The close correlation between these two variables suggests that good guidance can increase the motivation of nurses in the face of various tasks and situations.